Yellow fungus disease in a bearded dragon - Murillo, Daniel Felipe Barrantes; Watanabe, Tatiane Terumi Negrão; Perry, Sean; Mitchell, Mark; Piero, Fabio Del (Brazilian Journal of Veterinary Pathology, 2022)
An adult of unknown age, intact female bearded dragon (Pogona sp.) had multiple ulcerative foci in the skin, especially noted in the ventral neck and along the inguinal area. Due to the severity and extension of the epidermal/dermal lesions, as well as, the deleterious animal condition, the owners elected humane euthanasia and postmortem examination was performed.